MEDIA PEMBELAJARAN BERBASIS MACROMEDIA FLASH TERHADAP DAYA TARIK SISWA PADA PEMBELAJARAN TIK - Fricticarani, Ade; Rini, Ratu Yustika; Dayurni, Popi; Purnamasari, Alena (Jurnal Inovasi dan Teknologi Pendidikan, 2023)
This research is motivated by the lack of enthusiasm for learning and the attractiveness of students towards learning Information and Communication Technology (ICT) so that the lack of achievement and learning outcomes obtained and this study aims to determine how much influence the learning media has on student attractiveness. This study uses a quantitative approach with a descriptive survey method with all class XII students as a sample of 30 respondents and uses statistical tests, namely validity test, reliable test, normality test, simple linear regression test, f test and coefficient of determination test (R2). The results showed that there was a significant and positive influence simultaneously (simultaneously) between learning media (X) on student attractiveness (Y), with a value of Fcount > Ftable which was 54.529 > 4.20 which was at a significant level of F 0.001 and the results of the coefficient of determination test (R2) state that learning media (X) has an influence on student attractiveness (Y) of 66.1% so that the conclusions in this study can be stated that there is a significant effect of learning media using Macromedia Flash on student attractiveness with the statement Ho is rejected and Ha is accepted